Spoorbrug over de Koningshaven in aanbouw. Kopie van exemplaar bij Gemeentelijke Archiefdienst Rotterdam (1876)
Spoorbrug over de Koningshaven in aanbouw. Kopie van exemplaar bij Gemeentelijke Archiefdienst Rotterdam.